DESAIN KAPAL IKAN DENGAN BENTUK LAMBUNG CATAMARAN YANG MENGGUNAKAN SISTEM PENGGERAK LAYAR AN MESIN UNTUK MUATAN IKAN HIDUP - Parlindungan Manik; Eko Sasmito Hadi (Diponegoro University, 2010)
The Application Of Catamaran Hullform For The Fishing Vessel accorded to the leakage of the monohullform. The existence and the using of the lively fish hold could help the fisherman to decrease theoperational cost for about 11,8% to keep the fishes. Therefore the application of sail objected to reduce thebiggest cost operation component that is the fuel consumption. Catamaranhullform design for lively fish holdtook one hullform which has the best performance. The performance aspects in this case are the hydrostatic,ship resistance, stability and seakeeping.The research about catamaran fishing vessel design for lively fishes using sail and machine as the ship moveris expected to give the information about the hullform that has a better performance than the commonlyhullform and it could be an alternative to improve the fishing vessel hullform into the modern one.Accorded to the calculation result and analysis are gained the result that showed at the velocity of 12 knotsfrom some length dimension variations of fish hold for the catamaran fishing vessel with lively fish hold,variation of length of 2,0 meters could reduced the biggest ship’s resistance for about 3,99% between theother modification hullform and the ship’s resistance of standard hullform. Otherwise, by the stability aspectof any variation condition, fish hold length dimension variation at 2,0 meters had a better stability thananother fish hold length dimension and catamaran fishing vessel which used the commonly fish hold. Theinstallation of sail at the fish hold length dimension at 2,0 meters could reduce the power operation for about48,42% better than fishing vessel that used the commonly fish hold.